(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
The white carrot (Arracacia xanthorriza) is an Andean tuberous root of high nutritional value. It has a short post-harvest life which limits its commercialization. The use of edible coatings based on biopolymers constitutes an alternative to maintain the quality of postharvest products. The objective of this work was to evaluate the effect of applying a 1% starch coating on postharvest quality during refrigerated storage at 10±1°C and 80±2% relative humidity for 14 days. The roots were washed and disinfected; immersion was used as the application method. A completely randomized design and a factorial arrangement of the treatments were used, considering the factors: coating (with two levels, with coating (CR) and without coating (SR)), and time (with two levels: 7 and 14 days). It was evaluated: the color, expressed as L*, a* and b*, the intensity or Chroma and the tonality or Hue° were estimated; the percentage of fresh mass loss (%FML); the percentage of dry mass (%DM); the content of total soluble solids (TSS); pH and titratable acidity (TA) expressed as a percentage of malic acid. The coating affected the variables L*, a*, Hue°, pH and TA, presented a positive effect on the color of the roots. It shows great potential for use, and keeps quality chemical variables acceptable. To increase its effectiveness could be combined with another biopolymer or additives.